Substance abusers in jail: Health service breakdown in five New York jails - Lawrence, James E. (American journal of criminal justice, 1989)
The New York State Commission of Correction Medical Review Board studied five inmate mortalities which occurred between 1986 and 1989 in different New York State jails. The jails varied in size and in health care delivery capacity, but shared several characteristics, particularly severe overcrowding, high annual rates of population growth, and high concentrations of substance abusing inmates. Each inmate mortality case revealed an unprepared failure in health care delivery in which, absent such failure, the outcome may have been different. Influx of ever-increasing numbers of acutely and chronically ill substance abusers under overcrowded conditions intensifies demand on unprepared health care systems which increasingly break down. Jail health care systems should be evaluated in light of current population size and changing inmate health care needs.